Beyond Identity Wars for Recognition, Towards the Excluded Aspect of Subjectivity. On Vulnerability and the “Weak” Subject as an Opening for a Universalist Perspective on Education - Starego, Karolina (INSTED: Interdisciplinary Studies in Education & Society, 2025)
The paper contains a theoretical introduction addressing the paradigm of vulnerability – a way of thinking that might provide us with a new perspective on education. This perspective allows for an analysis of the current, diverse forms of cultural and identity wars, with a focus on the struggle for victim status. The politics of victimization is not reconstructed as a threat to stable democratic order, but as an epiphenomenon of a deeper ontological problem – the deficit of universality, especially in what is common and collectively shared. The perspective of vulnerability is treated as an alternative to other ways of constructing universalism, both within and outside of education.